Impact of a research-action on vaccination indicators in the state of Minas Gerais, Brazil - Janaina Fonseca Almeida Souza; Thales Philipe Rodrigues da Silva; Thais Moreira Oliveira; Aline Mendes Vimieiro; Antônia Maria da Silva Teixeira; Adriana Coelho Soares; Elice Eliane Nobre Ribeiro; Giselle Lima de Freitas; Eduarda Dantas Gaspar; Fernanda Penido Matozinhos (Revista de Saúde Pública, 2024)
ABSTRACT OBJECTIVE Analyze the impact of the state research-action project on immunization indicators (vaccination coverage – VC, homogeneity of vaccination coverage – HVC, dropout rate – DR, and risk rating) before and after the intervention in municipalities and priority Regional Health Administrations/Regional Health Superintendencies (RHA/RHS). METHODS The state research-action project was a before-after community clinical trial conducted in 212 municipalities belonging to eight RHA/RHS in the state of Minas Gerais, Brazil. The study sample comprised RHA/RHS with a decreasing trend for routine vaccination coverage in children under one year from 2015 to 2020. This study used secondary VC and DR data from 10 immunobiologicals recommended for children younger than two years from January to December 2021 (pre-intervention period, prior to the state research-action project) and from January to December 2022 (post-intervention period). The categorical variables were presented in proportions, and initially, a comparison was made between those of DR, HVC, and the risk rating for the transmission of vaccine-preventable diseases, according to the two periods (2021 and 2022), using the McNemar test. RESULTS All immunization indicators increased after conducting the research-action project. In 2021, 80.66% of the state’s municipalities had a risk rating for the transmission of vaccine-preventable diseases as “high and very high.” In 2022, the value reduced to 68.40%. CONCLUSIONS Risk rating for the transmission of vaccine-preventable diseases is an important mechanism to assist managers in defining priorities. The state research-action project used a method that enabled the construction and execution of unique action plans for each municipality, directing the improvement of immunization indicators in the state.